PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI YANG BERDAMPAK PADA KINERJA KARYAWAN - Pramudhita, Charisma Ayu; Meirisa, Faradila (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to analyze the influence that leadership style directly influences employee performance and work motivation, and can prove that work motivation has a direct effect on employee performance. The next goal is to find out that leadership style indirectly influences employee performance through motivation as an intervening variable. PT. XYZ is the object of this research. Determination of the sample is done by accidental sampling technique. The questionnaire was used as a means of collecting data distributed to employees who worked at PT. XYZ were 100 respondents. In this study using multiple linear regression analysis techniques. Hypothesis testing uses t test and F test. The results of the study show that leadership style has a positive and significant effect on employee performance, leadership style has a positive and significant effect on work motivation, work motivation has a positive effect on employee performance, leadership style has a positive effect on employee performance through motivation employee work.